2008
DOI: 10.1111/j.1467-9612.2008.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding, Phases, and Locality

Abstract: Abstract.  The central issue addressed here is syntactic locality, and the main proposal is that movement and anaphoric relations are governed by a unified concept of locality. The specific phenomena to be investigated are (i) infinitive constructions, in particular, Accusativus cum Infinitivo (AcI) complements, (ii) the German Possessor Dative Construction (PDC), with a dative nominal playing the role of both possessor and affectee, and (iii) binding, the conditions under which reflexive and nonreflexive pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Some of these analyses have been based either on overt movement (Hornstein , Kayne ) or on covert movement and feature checking (Reuland ), and some of them have argued that (at least certain aspects of) binding can be derived from Agree (e.g., Chomsky ; Fischer ; Gallego ; Heinat ; Hicks ; Reuland , ; and Rooryck & Vanden Wyngaerd ). Finally, a number of authors have also suggested that local binding domains should be reduced to phases (e.g., Canac‐Marquis , Heinat , Hicks , Lee‐Schoenfeld , Quicoli , and Safir ).…”
Section: Binding and Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these analyses have been based either on overt movement (Hornstein , Kayne ) or on covert movement and feature checking (Reuland ), and some of them have argued that (at least certain aspects of) binding can be derived from Agree (e.g., Chomsky ; Fischer ; Gallego ; Heinat ; Hicks ; Reuland , ; and Rooryck & Vanden Wyngaerd ). Finally, a number of authors have also suggested that local binding domains should be reduced to phases (e.g., Canac‐Marquis , Heinat , Hicks , Lee‐Schoenfeld , Quicoli , and Safir ).…”
Section: Binding and Phasesmentioning
confidence: 99%
“…In recent years, a number of authors have argued that local binding domains for anaphors are reducible to phases (e.g., Canac‐Marquis , Heinat , Hicks , Lee‐Schoenfeld , Quicoli , and Safir ). On such analyses, binding domains for local anaphors are CP and vP, because these are standardly assumed to constitute phases.…”
Section: Introductionmentioning
confidence: 99%
“…A number of linguists argue for the reducibility of local binding domains to phases (Lee-Schoenfeld 2004, Canac-Marquis 2005, Quicoli 2008, Hicks 2009, Safir 2011, Despić 2011, Antonenko 2012, Charnavel and Sportiche 2016. Some assume that the binding domains for anaphors are CPs/TPs and vPs, drawing on Chomsky's (2001Chomsky's ( , 2008 proposal that CPs and vPs constitute phases, while some others further argue that PPs and/or DPs can also be phases (Lee-Schoenfeld 2008;Hiraiwa 2005;Bošković 2012Bošković , 2014Despić 2015). The basic idea behind phase theory is that a sentence is decomposed into syntactic domains called phases, each of which is spelled out and independently sent off to the interface levels, Logical Form (LF) and Phonetic Form (PF), which assign semantic and phonetic/phonological interpretations to the utterance.…”
Section: Anaphoric Binding: Tp and Vp Phasesmentioning
confidence: 99%
“…The standard theory seems incapable of explaining why the reciprocal can surface but the reflexive cannot in such syntactic environments; this is because the two types of anaphors are predicted to appear in non-complementary positions, yet the reciprocal is licensed here but the reflexive is not. Such reflexive-reciprocal asymmetries, as I will show in sections 3 and 4, can be accounted for under three assumptions: the overt movement of the anaphoric distributor in reciprocals (see, for example, Heim, Lasnik, and May 1991, Carlson 1998, Büring 2005, which lends itself well to the copy theory of movement (Chomsky 1993); the binding-by-phase analysis (Lee-Schoenfeld 2004, 2008Quicoli 2008;Despić 2011Despić , 2015Antonenko 2012, among others); and the pronominal status of the reciprocal element indicating contrast, namely, the Arabic equivalent of the English other (Heim, Lasnik, and May 1991). I will also show that the phase-based model not only accounts for binding within possessive DPs or PPs, which will be argued to be phases, but also for binding within other phases like TPs or vPs (the phasehood of TP, which has been adopted from Antonenko (2012), will be discussed in the next section).…”
Section: Introductionmentioning
confidence: 99%
“…Since Chomsky () introduced the notion of a phase as the key to our understanding of locality a variety of proposals have been presented exploiting this notion for an understanding of locality on binding, for example Lee‐Schoenfeld (), Quicoli (), Despić (), Charnavel & Sportiche (). Phases are local domains.…”
Section: Towards a Comprehensive Theory Of Bindingmentioning
confidence: 99%